Geometrical Engineering of Giant Optical Dichroism in Rippled MoS2 Nanosheets. Issue 2 (18th November 2020) - Mennucci, Carlo; Mazzanti, Andrea; Martella, Christian; Lamperti, Alessio; Bhatnagar, Mukul; Lo Savio, Roberto; Repetto, Luca; Camellini, Andrea; Zavelani‐Rossi, Margherita; Molle, Alessandro; Buatier de Mongeot, Francesco; Della Valle, Giuseppe
Abstract: A cost effective method to tailor the optical response of large‐area nanosheets of 2D materials is described. A reduced effective metalayer model is introduced to capture the key‐role of the out‐of‐plane component of the dielectric tensor. Such a model indicates that the optical extinction of 2D materials can be strongly altered by controlling the geometry at the local (i.e., subwavelength) scale. In particular, a giant linear optical dichroism at normal incidence is demonstrated, with major features around the excitonic peaks, that can be tailored by acting on the average curvature and slope of the nanosheets. The approach is experimentally demonstrated in few‐layer MoS2 grown by chemical vapor deposition on cm‐scale anisotropic nanopatterned substrates prepared by a self‐assembling technique, based on defocused ion beam sputtering. Major variations in the photoluminescence spectrum as a function of the average curvature and slope are also revealed. A full‐vectorial numerical study beyond the effective metalayer model and comprising strain effects induced by the geometry turns out to be consistent with such a complex scenario. The results demonstrate that the extrinsic geometrical engineering definitely opens viable way to tailor the optical properties and modulate bandgap of low dimensional materials. Abstract : The MoS2 nanolayer with periodically rotated permittivity axes (sketch in the top panel) enables giant optical dichroism and control of dichroic ratio at normal incidence: for transverse polarized plane wave (TM), the optical extinction strongly depends on the average rotation angle whereas parallel polarized (TE) light is almost un‐affected by rotation of permittivity axes.